2019
DOI: 10.1155/2019/3139278
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Traditional and Nontraditional Indicators of Adiposity, Inflammation, and Monocyte Subtypes in Patients with Stable Coronary Artery Disease

Abstract: Background. Recruitment of monocytes and low-grade inflammation process are both involved in obesity and in atherosclerosis. Thus, the aim of this study was to evaluate the correlation among indicators of adiposity, monocyte subtypes, and inflammatory markers in patients with stable coronary artery disease (CAD). Methods. This was a cross-sectional study including 97 patients with stable CAD aged >40 years. Traditional anthropometric indicators of adiposity (body mass index (BMI); waist, hip, and neck circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Except for total CVD risk and risk age, the same variables were identified as independently associated variables with IL-6 levels above 1 pg/ml, with a multivariate linear regressionbackward analysis. Our results were in accordance with current scientific reports [40], [41], [42], [43], [44].…”
Section: Discussionsupporting
confidence: 93%
“…Except for total CVD risk and risk age, the same variables were identified as independently associated variables with IL-6 levels above 1 pg/ml, with a multivariate linear regressionbackward analysis. Our results were in accordance with current scientific reports [40], [41], [42], [43], [44].…”
Section: Discussionsupporting
confidence: 93%
“…Adipose tissue constitutes the major source of cytokines, chemokines, and metabolically active mediators known as adipokines 6 , 7 . It has been suggested that inflammation, which is induced by adipose tissue, is associated with osteoarthritis 8 10 , rheumatoid arthritis (RA) 11 13 , type 2 diabetes mellitus 14 17 , and coronary artery disease 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that an increased body mass index (BMI) and abdominal adiposity are associated with an increased risk of acute myocardial infarction and reduce the prognosis of patients with cardiovascular disease [25]. Also, there is an association between obesity and inflammation [12]. A recent study showed that light-emitting diode (LED) therapy protected against myocardial IRI-induced ventricular arrhythmia by suppressing microglial activation and the expression of inflammatory cytokines in the ischemic myocardium [26].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation has important roles in the onset and progression of cardiovascular disease. The increased secretion levels of inflammatory cytokines, including tumor necrosis factor-alpha (TNF-a), IL-10 and IL-12, are correlated with the development of CAD [12]. IL-6 is a mediator of the inflammatory and immune response, and the association between the IL-6 gene polymorphism and cardiovascular disease has been demonstrated [13].…”
Section: Introductionmentioning
confidence: 99%